Sex offender registration and community notification laws : an empirical evaluation / edited by Wayne A. Logan, J. J. Prescott. - Logan, Wayne A., 1960-; Prescott, J. J. (Cambridge University Press, 2021)
Despite being in existence for over a quarter century, costing multiple millions of dollars and affecting the lives of hundreds of thousands of individuals, sex offender registration and notification (SORN) laws have yet to be subject to a book-length treatment of their empirical dimensions - their premises, coverage, and impact on public safety. This volume, edited by Wayne Logan and J.J. Prescott, assembles the leading researchers in the field to provide an in-depth look at what have come to be known as 'Megan's Laws', offering a social science-based analysis of one of the most important, and controversial, criminal justice system initiatives undertaken in modern times.